Elastic magnetic abrasive and preparation method thereof

Through the magnetic abrasive designed with multi-layer functional structure, the problems of poor structural adaptability and insufficient surface fitting ability in the prior art are solved, and efficient removal and high-precision surface treatment in complex surface processing are achieved.

CN120555017APending Publication Date: 2025-08-29NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510637286.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

In the complex surface processing, existing magnetic abrasives have poor structural adaptability and insufficient surface fitting ability, making it difficult to take into account both grinding and polishing efficiency and surface quality.

Method used

The multi-layer functional structure design is adopted, including a ferromagnetic phase matrix, an elastic wrapping layer and abrasive phase particles. By introducing an elastic cladding layer and an embedded surface grinding particles, the coordinated control of magnetic response, flexible bonding and efficient removal is achieved.

Benefits of technology

It improves the adaptability and fit ability of magnetic abrasives in complex surface processing, improves processing accuracy and surface quality, and reduces the risk of damage to the workpiece surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120555017A_ABST
    Figure CN120555017A_ABST
Patent Text Reader

Abstract

The invention discloses an elastic magnetic grinding material and a preparation method thereof. The magnetic grinding material is characterized by comprising a ferromagnetic phase matrix, an elastic wrapping layer and grinding phase particles, the ferromagnetic phase matrix is formed by mixing and sintering iron powder and nickel powder according to a certain proportion, and provides controllable magnetic response characteristics and structure supporting capacity; the elastic wrapping layer wraps the surface of the ferromagnetic base body, is composed of one of polyurethane and epoxy resin, has the conceding characteristic and is effectively attached to a complex curved surface workpiece in the machining process. The grinding phase particles are one of diamond, aluminum oxide or silicon carbide and are fixedly embedded in the surface of the elastic wrapping layer, and efficient cutting and fine surface treatment are achieved. The magnetic abrasive has the functions of magnetic control adjustment, elastic attachment and efficient grinding, is suitable for magnetic control grinding and polishing machining of precise and complex parts, and can effectively improve the surface quality and machining adaptability. The invention further discloses a specific preparation method of the magnetic abrasive material, the process is simple and convenient, and adaptability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to abrasive preparation and abrasive processing (grinding, cutting, lapping, polishing, honing) technology, in particular to a magnetic abrasive capable of conforming to the surface of a complex curved workpiece, specifically to an elastic magnetic abrasive and a preparation method thereof. Background Art

[0002] With the development of high-end manufacturing, complex curved surface parts have been widely used in aerospace, energy and power, medical equipment and other fields, which also puts higher requirements on their surface quality and geometric accuracy. Magnetic abrasive finishing is a technology that uses a magnetic field to control magnetic abrasives to perform precision finishing on the surface of a workpiece. It has attracted widespread attention due to its flexible control capabilities and processing adaptability. Traditional magnetic abrasives are mostly composed of a rigid magnetic matrix and hard abrasives. Although they have certain removal capabilities, they have poor adhesion when processing complex free-form surfaces or irregular morphologies. They can easily lead to problems such as processing blind spots, scratches and surface stress concentration, which seriously restricts their application in the surface treatment of high-precision curved parts.

[0003] Chinese patent CN104669132A proposes a method for preparing a semi-solid viscoelastic magnetic grinding tool, which can reach any processing position such as dead corners and edges on the workpiece surface, avoiding the problem of low utilization and reuse rate of magnetic abrasive particles, and has certain adaptability, but the grinding body is large, the scope of application is small, and the matrix elasticity is low. Chinese patent CN103769278A proposes a method for preparing magnetic abrasive particles using high-energy ball milling, which uses mechanical energy to induce chemical reactions or induce changes in material organization, structure and performance, improve the uniformity of particle distribution, and enhance the bonding ability between interfaces, but particle agglomeration is difficult to avoid during the ball milling process. Chinese patent CN109890565A proposes a magnetizable abrasive particle and a preparation method thereof, which introduces a polyion layer on the surface of ceramic abrasive particles so that magnetic particles can be firmly attached to the surface of ceramic particles to form a composite magnetic abrasive with strong magnetic response ability and high bonding strength, but the magnetic layer is easy to wear and the preparation process is complicated.

[0004] Currently available magnetic abrasives have problems such as poor structural adaptability, insufficient surface adhesion, and difficulty in balancing grinding and polishing efficiency and surface quality, making it difficult to meet the requirements of high-precision complex surface processing. Summary of the Invention

[0005] The purpose of the present invention is to address the problems of poor structural adaptability, insufficient surface adhesion and difficulty in balancing surface quality in existing magnetic abrasives in complex surface processing. An elastic magnetic abrasive and a preparation method thereof are invented. The magnetic abrasive adopts a multi-layer functional structure design, introduces an elastic coating layer and surface-embedded abrasive particles, has a yielding characteristic, and can achieve coordinated control of magnetic response, soft adhesion and efficient removal. The magnetic abrasive is suitable for magnetic polishing and precision finishing of curved surface parts with complex curvature changes.

[0006] One of the technical solutions of the present invention is:

[0007] A magnetic abrasive with elasticity, characterized in that it consists of a ferromagnetic phase matrix 1, an elastic wrapping layer 2 and abrasive phase particles 3; the ferromagnetic phase matrix 1 is made of iron powder and nickel powder mixed and sintered in a certain proportion, providing controllable magnetic response characteristics (so that the abrasive has a certain adhesion force with the processed surface) and structural support capabilities; the elastic wrapping layer 2 is coated on the surface of the ferromagnetic phase matrix 1, and is made of one of polyurethane and epoxy resin, has a yielding characteristic, and effectively adheres to complex curved workpieces during processing; the abrasive phase particles 3 are one of diamond, aluminum oxide or silicon carbide, and are fixedly embedded in the surface of the elastic wrapping layer to achieve efficient cutting and fine surface treatment; the mass percentage of the abrasive phase particles 3 to the ferromagnetic phase matrix 1 can generally be 10%-30%.

[0008] The particle size of the iron powder in the ferromagnetic phase matrix 1 is distributed in the range of 20 μm-60 μm, the particle size of the nickel powder is distributed in the range of 10 μm-40 μm, and the mass ratio of the iron powder to the nickel powder is 60:40-80:20.

[0009] The thickness of the elastic wrapping layer 2 is 20 μm-50 μm.

[0010] The original particle size of the diamond, aluminum oxide or silicon carbide in the grinding phase particles 3 is distributed in the range of 30 μm to 45 μm.

[0011] The second technical solution of the present invention is:

[0012] A method for preparing elastic magnetic abrasive, characterized in that it comprises the following steps:

[0013] Step 1: Prepare a ferromagnetic phase matrix 1 by uniformly mixing iron powder and nickel powder in a ball mill according to a mass ratio, cold pressing under a pressure of 8 MPa, heating to 1100°C at 10°C / min under hydrogen protection, sintering for 4-6 hours, holding for 1-2 hours, step cooling, crushing, and sieving to obtain a ferromagnetic phase matrix 1 with a particle size of 100 μm-200 μm;

[0014] Step 2: Constructing the elastic wrapping layer 2: Immerse the ferromagnetic phase matrix 1 particles in 5% dilute hydrochloric acid for 5 minutes, neutralize them with dilute ammonia water, rinse them with deionized water until neutral, and then dry them. Prepare a wrapping solution, immerse the ferromagnetic phase matrix 1 particles in the solution, and pull them at a speed of 3 mm / s under ultrasonic assistance. Pre-dry the coated particles in an environment of 40-50°C for 30 minutes, and then heat cure them under certain conditions to obtain a preliminarily cured elastic wrapping layer 2 structure.

[0015] Step three, embed the grinding phase particles 3, pickle the grinding phase particles 3 with a 5wt% dilute nitric acid solution, neutralize them with dilute ammonia water, rinse them with deionized water until neutral and then dry them, mix them with the binder in a mass ratio of 3:1 and add 1wt% KH550 silane coupling agent, perform low-pressure plasma activation on the ferromagnetic phase matrix particles coated with an elastic layer, use electrostatic spraying to evenly attach the grinding phase particles to the surface of the elastic wrapping layer, preheat the matrix to 80°C, and roll the embedding depth to 1 / 3 of the particle size of the grinding phase particles 3. After the embedding is completed, the composite particles are placed under certain conditions for secondary curing treatment to form a stable bonding structure at the interface between the embedded particles and the coating layer, thereby obtaining an elastic magnetic abrasive with grinding particles firmly embedded on the surface.

[0016] The material of the elastic wrapping layer 2 is polyurethane, and the wrapping solution is a mixture of polyurethane prepolymer and HDI curing agent in a mass ratio of 4:1, dissolved in acetone to prepare a 20wt% solution, and 1wt% nano-SiO2 is added to enhance wear resistance. The material of the elastic wrapping layer is epoxy resin, and the wrapping solution is a mixture of epoxy resin and polyetheramine D230 curing agent in a mass ratio of 3:1, and 0.5wt% KH550 coupling agent is added to enhance interfacial bonding strength.

[0017] When the elastic wrapping layer 2 is made of polyurethane, thermal curing is performed at 80° C. for 3 hours. When the elastic wrapping layer is made of epoxy resin, thermal curing is performed at 120° C. for 2 hours.

[0018] When the elastic wrapping layer 2 is made of polyurethane, the bonding agent is a low-temperature curing polyurethane adhesive; when the elastic wrapping layer is made of epoxy resin, the bonding agent is an epoxy resin adhesive.

[0019] When the elastic wrapping layer 2 is made of polyurethane, the secondary curing should be carried out at 80° C. for 3 hours. When the elastic wrapping layer is made of epoxy resin, the secondary curing should be carried out at 120-150° C. for 2 hours.

[0020] The elastic magnetic abrasive of the present invention can be used for shaping and polishing complex curved surfaces of aircraft engine blades and titanium alloy medical implants.

[0021] The beneficial effects of the present invention are:

[0022] The ferromagnetic phase matrix of the magnetic abrasive of the present invention is formed by sintering iron powder and nickel powder in a proportional mixture, and has good magnetic permeability and magnetic retention ability. Under the action of an external magnetic field, it can respond quickly and form a stable chain-like magnetic brush structure, significantly improving the distribution uniformity of the magnetic abrasive in the processing area.

[0023] The elastic wrapping layer of the magnetic abrasive of the present invention is made of polymer materials such as polyurethane or epoxy resin, which can adapt to the changes in the surface microstructure of complex curved workpieces during the processing process, improve the processing coverage of the abrasive on difficult-to-process areas such as dead corners and edges, and effectively buffer the contact impact between the abrasive and the workpiece, reducing the risk of damage to the workpiece surface.

[0024] The grinding phase particles of the magnetic abrasive of the present invention adopt high hardness grinding particles such as diamond, aluminum oxide or silicon carbide, and are combined with low-pressure plasma activation and electrostatic spraying technology to achieve stable distribution and firm embedding of the particles on the surface of the elastic layer, with strong grinding ability and high processing precision.

[0025] The magnetic abrasive of the present invention organically combines a ferromagnetic phase matrix, an elastic coating layer and abrasive phase particles to construct a magnetic abrasive with integrated magnetic response, elastic buffering and efficient cutting, solving the problems of the existing magnetic abrasive having a single structure and poor adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the structure of the fixed abrasive tool of the present invention.

[0027] In the figure: 1-ferromagnetic phase aggregate; 2-elastic wrapping layer; 3-abrasive phase particles. DETAILED DESCRIPTION

[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments. Obviously, the embodiments described are only a part of the present invention, rather than all of the embodiments.

[0029] Example 1.

[0030] An elastic magnetic abrasive material comprises a ferromagnetic phase matrix 1, an elastic wrapping layer 2, and abrasive phase particles 3. Figure 1 The specific preparation method is as follows:

[0031] 1. Prepare a ferromagnetic phase matrix by uniformly mixing iron powder and nickel powder (160 g of iron powder with a particle size of 20 μm and 40 g of nickel powder with a particle size of 10 μm) in a ball mill according to a mass ratio, cold-pressing the mixture under a pressure of 8 MPa, heating the mixture to 1100°C at a rate of 10°C / min under hydrogen protection, sintering the mixture for 4 hours, holding the mixture for 1 hour, and step-cooling the mixture (step-cooling refers to cooling from 1100°C to 900°C, then from 900°C to 600°C, and then cooling the mixture to room temperature to prevent particle breakage. In a specific implementation, the mixture can also be directly cooled to room temperature, the same below). After crushing and sieving, a ferromagnetic phase matrix with a particle size of 100 μm was obtained.

[0032] 2. Constructing an elastic wrapping layer: The ferromagnetic phase matrix particles were immersed in 5% dilute hydrochloric acid for 5 minutes, neutralized with dilute ammonia, rinsed with deionized water until neutral, and then dried. The wrapping solution was prepared by mixing a polyurethane prepolymer and an HDI curing agent in a 4:1 mass ratio, dissolved in acetone to prepare a 20wt% solution, and 1wt% nano-SiO2 was added to enhance wear resistance. The matrix particles were immersed in the solution and pulled at a speed of 3mm / s under ultrasonic assistance. The coated particles were pre-dried at 40°C for 30 minutes and then thermally cured at 80°C for 3 hours to obtain a preliminarily cured elastic wrapping layer structure with a thickness of 20μm.

[0033] 3. Embedding the grinding phase particles, using 5wt% dilute nitric acid solution to pickle the diamond particles (i.e., grinding phase particles, particle size 30μm, weight 30g, accounting for 15%), neutralized with dilute ammonia water, rinsed with deionized water until neutral and then dried, mixed with a low-temperature curing polyurethane adhesive (i.e., a mixture of polyurethane prepolymer and HDI curing agent) in a mass ratio of 3:1 and added with 1wt% KH550 silane coupling agent, and the ferromagnetic phase matrix particles coated with the elastic layer were low-pressure plasma activated, and the grinding phase particles were evenly attached to the surface of the elastic wrapping layer by electrostatic spraying. After preheating the substrate to 80°C and curing for 3 hours, the roller embedding depth reached 1 / 3 of the diamond particle size. The composite particles after embedding were placed at 80°C for 3 hours for secondary curing to form a stable bonding structure at the interface between the embedded particles and the coating layer, thereby obtaining an elastic magnetic abrasive with abrasive particles firmly embedded on the surface.

[0034] Magnetic abrasive particles were screened to obtain elastic magnetic abrasive with a particle size of 140-180 μm. The root area of ​​a TC4 titanium alloy blade (for an aeroengine) was machined using an ABB robotic platform at a spindle speed of 750 rpm, a feed rate of 5 mm / min, a machining gap of 2 mm, and a polishing pressure of 0.018 MPa. The surface finish using this magnetic abrasive was reduced from Ra 0.250 μm before polishing to Ra 0.042 μm.

[0035] Example 2.

[0036] A magnetic abrasive with elasticity, comprising a ferromagnetic phase matrix, an elastic coating, and abrasive phase particles. The abrasive comprises 180 grams of 60 μm iron powder, 120 grams of 40 μm nickel powder, an epoxy resin elastic coating, and 30 grams of 45 μm aluminum oxide abrasive particles (accounting for 10%). The specific preparation method is as follows:

[0037] 1. Prepare the ferromagnetic phase matrix by uniformly mixing iron powder and nickel powder in a ball mill according to the mass ratio, cold pressing under a pressure of 8 MPa, sintering at a rate of 10°C / min to 1100°C for 6 hours under hydrogen protection, holding the temperature for 2 hours, step cooling, crushing, and sieving to obtain a ferromagnetic phase matrix with a particle size of 200 μm;

[0038] 2. Constructing an elastic wrapping layer: immerse the ferromagnetic phase matrix particles in 5% dilute hydrochloric acid for 5 minutes, neutralize them with dilute ammonia water, rinse them with deionized water until neutral, and then dry them. Prepare a wrapping solution with a mixture of epoxy resin and polyetheramine D230 curing agent in a 3:1 mass ratio, add 0.5wt% KH550 coupling agent, immerse the matrix particles in the wrapping solution, and pull them at a speed of 3mm / s under ultrasonic assistance. Pre-dry the coated particles in a 50°C environment for 30 minutes, and then heat cure them at 120°C for 2 hours to obtain a preliminarily cured elastic wrapping layer structure with a thickness of 50μm.

[0039] 3. Embedding the abrasive phase particles, using 5wt% dilute nitric acid solution to pickle the alumina particles (particle size 45μm, weight 30g), neutralize them with dilute ammonia water, rinse them with deionized water until neutral and then dry them, mix them with epoxy resin adhesive in a mass ratio of 3:1 and add 1wt% KH550 silane coupling agent, and perform low-pressure plasma activation on the ferromagnetic phase matrix particles coated with the elastic layer. Use electrostatic spraying to evenly attach the abrasive phase particles to the surface of the elastic wrapping layer, preheat the matrix to 80°C and heat cure for 3 hours, and then roll the embedding depth to 1 / 3 of the diamond particle size. After the embedding is completed, the composite particles are placed at 150°C for 2 hours for secondary curing treatment to form a stable bonding structure at the interface between the embedded particles and the coating layer, thereby obtaining an elastic magnetic abrasive with abrasive particles firmly embedded on the surface.

[0040] Magnetic abrasive particles were screened to obtain elastic magnetic abrasive with a diameter of 250-320 μm. The back area of ​​a Ti6Al4V titanium alloy blade was machined using an ABB robotic platform at a spindle speed of 750 rpm, a feed rate of 5 mm / min, a machining gap of 2.5 mm, and a polishing pressure of 0.032 MPa. The surface finish using this magnetic abrasive was reduced from Ra 0.860 μm before polishing to Ra 0.182 μm.

[0041] Example 3.

[0042] A magnetic abrasive with elasticity, comprising a ferromagnetic phase matrix, an elastic coating, and abrasive phase particles. The matrix comprises 175 grams of 40μm iron powder, 75 grams of 25μm nickel powder, an epoxy resin elastic coating, and 75 grams of 30μm silicon carbide abrasive particles (accounting for 30%). The specific preparation method is as follows:

[0043] 1. Prepare the ferromagnetic phase matrix by uniformly mixing iron powder and nickel powder in a ball mill according to the mass ratio, cold pressing under a pressure of 8 MPa, heating to 1100°C at a rate of 10°C / min under hydrogen protection, sintering for 6 hours, holding at that temperature for 1 hour, step cooling, crushing, and sieving to obtain a ferromagnetic phase matrix with a particle size of 150 μm;

[0044] 2. Constructing an elastic wrapping layer: immerse the ferromagnetic phase matrix particles in 5% dilute hydrochloric acid for 5 minutes, neutralize them with dilute ammonia water, rinse them with deionized water until neutral, and then dry them. Prepare a wrapping solution with a mixture of epoxy resin and polyetheramine D230 curing agent in a 3:1 mass ratio, add 0.5wt% KH550 coupling agent, immerse the matrix particles in the solution, and pull them at a speed of 3mm / s under ultrasonic assistance. Pre-dry the coated particles in a 50°C environment for 30 minutes, and then heat cure them at 120°C for 2 hours to obtain a preliminarily cured elastic wrapping layer structure with a thickness of 40μm.

[0045] 3. Embed the grinding phase particles, pickle the silicon carbide particles with a 5wt% dilute nitric acid solution, neutralize them with dilute ammonia water, rinse them with deionized water until neutral, and then dry them. Mix them with epoxy resin adhesive in a mass ratio of 3:1 and add 1wt% KH550 silane coupling agent. Perform low-pressure plasma activation on the ferromagnetic phase matrix particles coated with an elastic layer, and use electrostatic spraying to evenly attach the grinding phase particles to the surface of the elastic wrapping layer. Preheat the matrix to 80°C, and roll the embedding depth to 1 / 3 of the diamond particle size. After embedding, place the composite particles at 120°C for a secondary curing treatment for 2 hours to form a stable bonding structure at the interface between the embedded particles and the coating layer, thereby obtaining an elastic magnetic abrasive with abrasive particles firmly embedded on the surface.

[0046] The magnetic abrasive particles were screened to obtain elastic magnetic abrasives with a diameter of 180-250 μm. This magnetic abrasive was used to polish titanium alloy medical implants using magnetic-assisted single-side polishing equipment. The surface roughness was reduced from Ra 0.320 μm to Ra 0.158 μm at a spindle speed of 1000 rpm, a feed rate of 10 mm / min, a machining gap of 2.5 mm, and a polishing pressure of 0.026 MPa.

[0047] The above is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.

[0048] The parts not involved in the present invention are the same as the existing technology or can be implemented by using the existing technology.

Claims

1. A magnetic abrasive with elasticity, characterized in that: It consists of a ferromagnetic phase matrix (1), an elastic wrapping layer (2) and abrasive phase particles (3); the ferromagnetic phase matrix (1) is made of iron powder and nickel powder mixed in a certain proportion and sintered, providing controllable magnetic response characteristics and structural support capabilities; the elastic wrapping layer (2) is coated on the surface of the ferromagnetic phase matrix (1), and is made of one of polyurethane and epoxy resin, has a yielding characteristic, and effectively fits complex curved workpieces during processing; the abrasive phase particles (3) are one of diamond, aluminum oxide or silicon carbide, and are fixedly embedded in the surface of the elastic wrapping layer to achieve efficient cutting and fine surface treatment.

2. The elastic magnetic abrasive according to claim 1, characterized in that: The particle size of the iron powder in the ferromagnetic phase matrix (1) is distributed in the range of 20 μm to 60 μm, the particle size of the nickel powder is distributed in the range of 10 μm to 40 μm, and the mass ratio of the iron powder to the nickel powder is 60:40 to 80:

20.

3. The elastic magnetic abrasive according to claim 1, characterized in that: The thickness of the elastic wrapping layer (2) is 20 μm-50 μm.

4. The elastic magnetic abrasive according to claim 1, characterized in that: The original particle size of diamond, aluminum oxide or silicon carbide in the grinding phase particles is distributed in the range of 30 μm to 45 μm.

5. A method for preparing the elastic magnetic abrasive according to claim 1, characterized in that: It includes the following steps: Step 1: Prepare a ferromagnetic phase matrix by uniformly mixing iron powder and nickel powder in a ball mill according to the mass ratio, cold pressing under a pressure of 8 MPa, heating to 1100°C at 10°C / min under hydrogen protection for 4-6 hours, holding the temperature for 1-2 hours, step cooling, crushing, and sieving to obtain a ferromagnetic phase matrix with a particle size of 100 μm-200 μm; Step 2: Constructing an elastic wrapping layer: immerse the ferromagnetic phase matrix particles in 5% dilute hydrochloric acid for 5 minutes, neutralize them with dilute ammonia water, rinse them with deionized water until neutral, and then dry them. Prepare a wrapping solution, immerse the ferromagnetic phase matrix particles in the solution, and pull them at a speed of 3 mm / s under ultrasonic assistance. Pre-dry the coated particles in an environment of 40°C-50°C for 30 minutes, and then heat cure them under certain conditions to obtain a preliminarily cured elastic wrapping layer structure. Step three, embedding the grinding phase particles, pickling the grinding phase particles with 5wt% dilute nitric acid solution, neutralizing them with dilute ammonia water, rinsing them with deionized water until neutral and then drying them, mixing them with the binder in a mass ratio of 3:1 and adding 1wt% KH550 silane coupling agent, low-pressure plasma activation of the ferromagnetic phase matrix particles coated with the elastic layer, electrostatic spraying to evenly attach the grinding phase particles to the surface of the elastic wrapping layer, preheating the matrix to 80°C, rolling and embedding to a depth of 1 / 3 of the particle size of the grinding phase particles, and placing the composite particles after embedding under certain conditions for secondary curing treatment to form a stable bonding structure at the interface between the embedded particles and the coating layer, thereby obtaining an elastic magnetic abrasive with abrasive particles firmly embedded on the surface.

6. The preparation method according to claim 5, characterized in that The elastic wrapping layer material is polyurethane, and the wrapping solution is prepared by mixing polyurethane prepolymer and HDI curing agent in a mass ratio of 4:1, dissolved in acetone to prepare a 20wt% solution, and 1wt% nano-SiO2 is added to enhance wear resistance; or the elastic wrapping layer material is epoxy resin, and the wrapping solution is prepared by mixing epoxy resin and polyetheramine D230 curing agent in a mass ratio of 3:1, and 0.5wt% KH550 coupling agent is added to enhance interfacial bonding strength.

7. The preparation method according to claim 5, characterized in that When the elastic wrapping layer material is polyurethane, thermal curing is performed at 80° C. for 3 hours. When the elastic wrapping layer material is epoxy resin, thermal curing is performed at 120° C. for 2 hours.

8. The preparation method according to claim 5, characterized in that When the elastic wrapping layer material is polyurethane, the bonding agent is a low-temperature curing polyurethane adhesive; when the elastic wrapping layer material is epoxy resin, the bonding agent is an epoxy resin adhesive.

9. The preparation method according to claim 5, characterized in that When the elastic wrapping layer material is polyurethane, the secondary curing should be carried out at 80° C. for 3 hours; when the elastic wrapping layer material is epoxy resin, the secondary curing should be carried out at 120° C.-150° C. for 2 hours.

10. An elastic magnetic abrasive according to any one of claims 1 to 4, characterized in that: The magnetic abrasive is used for shaping and polishing complex curved surfaces of aircraft engine blades and titanium alloy medical implants.

Citation Information

Patent Citations

  • High-energy ball-milling preparation method for magnetic abrasive particles

    CN103769278A

  • Viscoelastic magnetic grinding tool and preparation method thereof

    CN104669132A

  • Magnetizable abrasive particle and method of making the same

    CN109890565A